Hacking the Lipidome: New Ferroptosis Strategies in Cancer Therapy - Varynskyi, B.; Schick, J. A.; Варинський, Борис Олександрович (My University, 2024)
The concept of redirecting metabolic pathways in cancer cells for therapeutic purposes has become a prominent theme in recent research. Now, with the advent of ferroptosis, a new chink in the armor has evolved that allows for repurposing of ferroptosis-sensitive lipids in order to trigger cell death. This review presents the historical context of lipidomic and metabolic alterations in cancer cells associated with ferroptosis sensitization. The main proferroptotic genes and pathways are identified as therapeutic targets for increasing susceptibility to ferroptosis. In this review, a particular emphasis is given to pathways in cancer cells such as de novo lipogenesis, which has been described as a potential target for ferroptosis sensitization. Additionally, we propose a connection between ketolysis inhibition and sensitivity to ferroptosis as a new vulnerability in cancer cells. The main proferroptotic genes and pathways have been identified as therapeutic targets for increasing susceptibility to ferroptosis. Proferroptotic metabolic pathways and vulnerable points, along with suggested agonists or antagonists, are also discussed. Finally, general therapeutic strategies for ferroptosis sensitization based on the manipulation of the lipidome in ferroptosis-resistant cancer cell lines are proposed.
Keywords: ferroptosis; cancer cells; de novo lipogenesis; ketolysis; lipidomics; metabolic reprogramming; cancer treatment; therapeutic resistance